Using Google Street View to investigate the association between street greenery and physical activity - Lu, Yi (Landscape and urban planning, 2019)
•The quality and quantity of street greenery are associated with increased recreational green physical activity.•Using Google Street View can accurately estimate residents’ daily exposure of street greenery.•The findings also help us recognize the impacts of environmental factors on residents’ physical activity. Urban greenspaces have been demonstrated to have associations with physical activity and health. Yet empirical studies have almost exclusively focused on parks rather than street, although streets are among the most popular venues for physical activity and street greenery is an indispensable component of urban greenspaces. Even fewer greenspace-physical activity studies have objectively assessed eye-level street greenery. By using free Google Street View images, this study assessed both the quantity and quality of street greenery and associated them with the recreational physical activity occurring in green outdoor environments of 1390 participants in 24 housing estates in Hong Kong. After controlling for socio-demographic characteristics and other built environment factors, multilevel regression models revealed that the quality and quantity of street greenery were positively linked to recreational physical activity. Our finding is important for interpretations of the operational mechanisms between street greenery and health benefits because it demonstrates that physical activity is an intermediate health-related outcome. The findings also reveal the influences of eye-level street greenery on residents’ physical activity levels and hence contribute to the development and implementation of healthy cities to stimulate physical activity.